2017
DOI: 10.1101/179556
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Brain state and polarity dependent modulation of brain networks by transcranial direct current stimulation

Abstract: Transcranial direct current stimulation (TDCS) has been widely used to improve cognitive function. However, current deficiencies in mechanistic understanding hinders wider applicability. To clarify its physiological effects, we acquired fMRI whilst simultaneously acquiring TDCS to the right inferior frontal gyrus (rIFG) of healthy human participants, a region involved in coordinating activity within brain networks. TDCS caused widespread modulation of network activity depending on brain state (‘rest’ or choice… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(42 citation statements)
references
References 60 publications
5
37
0
Order By: Relevance
“…The study protocol is selected based on several assumptions and hypotheses such as time course of tDCS effect (Nitsche & Paulus, 2000), cellular mechanism of stimulation (Bikson et al, 2004;Rahman et al, 2013), state dependency of tDCS as a subthreshold stimulation method (Hsu, Juan, & Tseng, 2016;Li et al, 2019), and dose-response relationship. Ultimately, these considerations get to the heart of how tDCS research benefits from functional MR imaging and how to address inherent challenges in experimental design.…”
Section: Tdcs-mr Imaging: Trial Design Parameter Spacementioning
confidence: 99%
“…The study protocol is selected based on several assumptions and hypotheses such as time course of tDCS effect (Nitsche & Paulus, 2000), cellular mechanism of stimulation (Bikson et al, 2004;Rahman et al, 2013), state dependency of tDCS as a subthreshold stimulation method (Hsu, Juan, & Tseng, 2016;Li et al, 2019), and dose-response relationship. Ultimately, these considerations get to the heart of how tDCS research benefits from functional MR imaging and how to address inherent challenges in experimental design.…”
Section: Tdcs-mr Imaging: Trial Design Parameter Spacementioning
confidence: 99%
“…Peak electric field was confirmed via computational, finite element method (FEM) head modelling as in Li et al [9] (Fig 1d). Outside the scanner, participants had two 15-second blocks of anodal and cathodal tDCS, and were asked to rate sensations of itching, pain, metallic taste, burning, anxiety, and tingling on a 1-5 scale, with 1=nil and 5=unbearable.…”
Section: Delivery Of Tdcsmentioning
confidence: 60%
“…Brain state is a key factor determining the physiological response to tDCS. Previous work from our group and others have found that brain state influences the brain network effects of tDCS in healthy controls [7] [8] [9]. Specifically, our previous tDCS-fMRI work shows that tDCS reinforces the underlying pattern of brain network activity, and that this interacts with stimulation polarity [9].…”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations